Cabozantinib as the causative agent of high-grade fever in a patient with a background of metastatic clear cell renal cell carcinoma: a case report - H. M. N. Chen; M. Morris; P. M. Manders (Journal of Medical Case Reports, 2020)
Abstract Background Fever, as an adverse event, is well documented in a wide array of drugs including multiple tyrosine kinase inhibitors however, it is not a previously well described consequence of the novel multi-targeted tyrosine kinase inhibitor, cabozantinib. Case presentation In this paper we document the first detailed review of high-grade fevers in a 54 year old male (Caucasian) with a background of metastatic clear cell renal cell carcinoma recently commenced on cabozantinib. After detailed investigation, we exclude infection and other common causes of fever as the causative agent and further, definitively resolve the recurrent fever by ceasing cabozantinib and starting a short course of oral corticosteroids. Conclusions We have demonstrated that cabozantinib should always be considered in the aetiology of high-grade fever in relevant patients. Further, we demonstrate that temporary cessation of cabozantinib and a course of short-term steroids can induce resolution of fever and allow for recommencement of cabozantinib safely thereafter.